Severe pulmonary hypertension–interstitial lung disease presenting as right ventricular failure: stabilisation with intravenous prostacyclin and maintenance with inhaled prostacyclin - Raj Parikh; Alysse Thomas; Aldo Sharofi; Niala Moallem; Garrett Fiscus; Harrison W. Farber (ERJ Open Research, 2024)
Background Pulmonary hypertension (PH) leads to increased morbidity and mortality in interstitial lung disease (ILD). While the INCREASE trial highlighted the use of inhaled prostacyclin in PH-ILD patients, such therapy may be inadequate when right ventricular failure (RVF) is also present. In this study, we report the use of intravenous prostacyclin in three PH-ILD patients to stabilise right ventricular (RV) function, with a subsequent transition to maintenance therapy with inhaled prostacyclin. Methods We evaluated three consecutive PH-ILD patients with RVF. RV afterload and pulmonary vascular resistance (PVR) were treated with intravenous prostacyclin during the induction phase of the therapy. Patients transitioned from intravenous prostacyclin to the maintenance phase of the treatment with inhaled prostacyclin once three transition criteria were met: cardiac index (CI) >2 L·min−1·m−2, PVR <7 Wood units (WU) and tricuspid annular plane systolic excursion (TAPSE) change >1 mm or TAPSE >1.6 cm. Results Pre-treatment parameters for the three patients were a mean PVR of 14.3 WU, a mean Fick CI of 1.8 L·min−1·m−2 and a mean TAPSE of 1.4 cm. The average intravenous prostacyclin dose at the time of transition to maintenance therapy was 20.7 ng·kg−1·m−2 of treprostinil. At 3-months follow-up, the mean PVR was 6.3 WU, Fick CI 2.2 L·min−1·m−2 and TAPSE 1.7 cm. Conclusion This case series of three PH-ILD patients with RVF introduces the concept of an initial intravenous prostacyclin induction phase, followed by a transition to maintenance therapy with inhaled prostacyclin. Further development of this treatment algorithm with a refinement of the transition criteria, potential testing in a clinical trial and a longer-term follow-up period is warranted to improve the outcomes of advanced PH-ILD patients with concomitant RVF.